2008
DOI: 10.1088/0268-1242/23/9/095004
|View full text |Cite
|
Sign up to set email alerts
|

Cu-doped ZnO-based p–n hetero-junction light emitting diode

Abstract: Copper-doped p-ZnO thin films (Cu:ZnO) were grown on α-Al 2 O 3 (0 0 0 1) and 6H:SiC(0 0 0 1) single crystal substrates by plasma-assisted molecular beam epitaxy. A p-n hetero-junction with p-Cu:ZnO/n-6H:SiC was successfully fabricated and demonstrated as a greenish-blue light emitting diode (LED). The rectifying I-V curve along with the matching photoluminescence and electroluminescence emissions characterizes the fabricated p-n hetero-junction LED. The Cu cell temperature (T Cu ) and the post-deposition anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…As one of the most important binary TMO at present, ZnO has wide applications in electronics, optics, optoelectronics, spintronics and energy generators, which can be achieved through band gap engineering, dopant incorporation, defect engineering, or heterostructure engineering [4,5]. For the doped ZnO compounds, copper-doped ZnO (ZnO:Cu) has captured considerable attention in magnetic semiconductors [6], light emitting diodes [7], surface acoustic wave [8], and optical switching [9,10] applications. Cu ions are well known as electron traps in ZnO films and they can increase the resistivity of ZnO from semiconducting to insulating-like properties [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most important binary TMO at present, ZnO has wide applications in electronics, optics, optoelectronics, spintronics and energy generators, which can be achieved through band gap engineering, dopant incorporation, defect engineering, or heterostructure engineering [4,5]. For the doped ZnO compounds, copper-doped ZnO (ZnO:Cu) has captured considerable attention in magnetic semiconductors [6], light emitting diodes [7], surface acoustic wave [8], and optical switching [9,10] applications. Cu ions are well known as electron traps in ZnO films and they can increase the resistivity of ZnO from semiconducting to insulating-like properties [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…p-type ZnO is achievable but difficult to control and stabilize over time. Examples include p-i-n homojunctions, 50 p-n homojunction light emitting diodes, 51 and p-Cu:ZnO/n-6 H:SiC p-n heterojunctions, 52 each of which emit light with electric current. Very recently, Liu et al have demonstrated lasing within ZnO nanorods.…”
Section: Defect Roles In Achieving Controlled Dopingmentioning
confidence: 99%
“…It is possible that Cu atoms can replace either substitutional or interstitial Zn atoms in the ZnO lattice creating structural deformations. 4,5 Cu significantly affects the electrical, chemical, structural and optical properties of ZnO, and the study of the electronic state of Cu in ZnO has been the subject of interest for a long time. [6][7][8][9] Various techniques for the preparation of ZnO films have been used such as electrochemical deposition, 10 19 screen printing, 20 etc.…”
Section: Introductionmentioning
confidence: 99%